2010
DOI: 10.1007/s10815-010-9468-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro maturation of oocytes via the pre-fabricated self-assembled artificial human ovary

Abstract: Purpose Create a 3-Dimensional artificial human ovary to mature human oocytes. Methods Theca and granulosa cells were isolated from antral follicles of reproductive-aged women, seeded into micro-molded gels and self-assembled into complex 3D microtissues. Immunohistochemistry and live-dead staining confirmed theca cell identity and cellular viability at one week respectively. Placement of granulosa cell spheroids or cumulus-oocyte complexes into theca cell honeycomb openings resulted in creation of an artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…For example, using a 3-dimensional (3D) in vitro maturation (IVM) culture system, it has been demonstrated that combining the follicular subtypes ( e.g . granulosa and oocytes, with or without theca cells) creates an ‘artificial’ ovarian environment which supports human oocyte maturation (Krotz et al, 2010). Similar approaches have been reported using cells and tissues from mice, rats, non-human primates and humans (Xu et al, 2006; Laronda et al, 2014; Hornick et al, 2012; Xu et al, 2009; Luyckx et al 2013, 2014; Díaz-García and Herraiz, 2014, Liu et al, 2013, 2014; Kniazeva et al, 2015), albeit with the goal of follicle maturation rather than endocrine function.…”
Section: Discussionmentioning
confidence: 99%
“…For example, using a 3-dimensional (3D) in vitro maturation (IVM) culture system, it has been demonstrated that combining the follicular subtypes ( e.g . granulosa and oocytes, with or without theca cells) creates an ‘artificial’ ovarian environment which supports human oocyte maturation (Krotz et al, 2010). Similar approaches have been reported using cells and tissues from mice, rats, non-human primates and humans (Xu et al, 2006; Laronda et al, 2014; Hornick et al, 2012; Xu et al, 2009; Luyckx et al 2013, 2014; Díaz-García and Herraiz, 2014, Liu et al, 2013, 2014; Kniazeva et al, 2015), albeit with the goal of follicle maturation rather than endocrine function.…”
Section: Discussionmentioning
confidence: 99%
“…After the micro-molded gels are seeded, the cells settle to the bottom of the recesses, are unable to attach to the nonadhesive hydrogel, and cell-to-cell interactions drive the formation of a single spheroid in each recess. This technology has been used to form spheroids using many different cell types including primary cells and cell lines from a variety of tissues including, skin, brain, ovary, liver, heart, and breast 9, 49, 51-53 . The method can be scaled up to create up to 822 spheroids in a single mold, with homogenous shape, size, and cell composition.…”
Section: Methodsmentioning
confidence: 99%
“…Another method has been proposed for self-assembly of three-dimensional microtissues from granulosa and theca cells isolated from adult human ovaries. The cells are seeded into the recesses of micromolded agarose gels (107) and more closely recreate the three-dimensional interaction between the granulosa cells, theca cells, and oocyte that is critical to follicular maturation. These artificial ovaries could be used to mature early antral oocytes, and serve as tools for testing follicular physiology and toxicology in preclinical drug development.…”
Section: Emerging Opportunitiesmentioning
confidence: 99%